INFLUENCE OF LECTURERS’ COMMUNICATION SKILLS ON STUDENTS’ ACADEMIC PERFORMANCE IN PUBLIC UNIVERSITIES IN RIVERS STATE - Egbo, Rose (International Journal of Educational Excellence and Innovation, 2024)
The study examined the influence of lecturers’ communication skills on students’ academic performance in public universities in Rivers State. The study adopted a descriptive survey research design. Two research questions and two hypotheses guided the study. The population of the study consisted of 190 respondents (93 lecturers and 97 students) from the three public universities in Rivers State, Nigeria. The sample size for the study consisted of 76 respondents (37 lecturers and 39 students); representing 40% of the total population size, simple random sample technique was used. A self-structured questionnaire items structured on a validated four-point rating scales was used. The reliability coefficient of 0.84 was obtained. Data obtained was analyzed using the mean and Z-test. Specifically, the was used to answer the research questions while the Z-test was to test the hypotheses at 0.05 level of significance. It was recommended that the lecturers’ incentive should always be given to them in order for them to put in their best for the betterment of the students and it will enhance and ensure and quality educational assessment in the universities. The welfare of the lecturers will strengthen them for effectiveness, for instance, if they are promoted as when due, they are given opportunities for their professional growth, provision of welfare services that are currently lacking optimal performance of the lecturers and students in public universities in Rivers State.